Some thermodynamic effects in thin film adhesion - Chornous, A.M.; KirikI, G.V.; Protsenko, Yu.; Stadnik, A.D. (Functional Materials, 2005)
The following thermodynamic effects have been studied in experiment: the normal adhesion of Ge films as a function of the surface energy of substrate (glass, mica, Al, Cu); the normal adhesion of Ge, Al, Cu and Cr films to Cu and (001) NaCI substrates as a function of the specific surface energy of the film; the dimensional dependence of Cu and Cr adhesion within thickness range of 20 to 250 nm; effect of finely dispersed ferromagnetic and weakly magnetic powders used as fillers in partially crystallized polymer substrates with relatively low specific surface energy on Al film adhesion. An increase in the film thickness as well as in the specific surface energy of the substrate and the film has been found to result in weakened adhesion.